PENYULUHAN KESEHATAN TENTANG MANFAAT ZUMBA DANCE DAN AEROBIC EXERCISE TERHADAP CONTROLLING BLOOD PRESURE DI DESA NGRIMBI KECAMATAN BARENG KABUPATEN JOMBANG - Nurul Agustin (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2022)
Hypertension is a condition when the blood pressure in the blood vessels is chronically elevated. This can happen because the heart works harder to pump blood to meet the body's needs for oxygen and nutrients. If left unchecked, this disease can interfere with the function of other organs, especially vital organs such as the heart and kidneys. Hypertension is a silent killer, because it occurs without any symptoms or is asymptomatic. Hypertension can occur due to several risk factors, namely family history, poor living habits, poor dietary patterns and poor sleep quality. According to the Health Promotion Model, individual health behavior can arise and be maintained because of a commitment to perform a behavior. In addition to commitment, individual health behavior is also influenced by circumstances that lead to an individual's desire to behave in a certain way as planned.